Studenci i studentki wobec feminatywów. Analiza poziomu akceptacji żeńskich nazw zawodów i stanowisk - Klon, Weronika; Waszyńska, Katarzyna; Zachorska, Martyna (Kultura-Społeczeństwo-Edukacja, 2025)
The debate over the feminine forms of profession and function names, which has been going on for more than a century, has been strengthened in recent years by the debate about non-discriminatory language. More institutions, including educational ones such as universities, are adopting anti-discrimination policies, of which language guidelines are a part. The article summarizes the first stage of the study, which aimed to investigate the level of acceptance of feminitives (feminine job names) referring to professions and functions (113 lexemes) in the academic community of Adam Mickiewicz University in Poznan. The survey was conducted using the Qualtrics online platform. The task of the respondents was to provide their level of acceptance for the usage of individual feminitives on a sixpoint scale from 0 to 5. Some feminitives homonymous with common names (including drukarka, marynarka, dziekanka; ENG: female printer, female sailor, female dean) and feminitives referring to functions of high prestige (including dziekana, premiera, kapitanka; ENG: female dean, female prime minister, female captain) were rated as the least acceptable. The most prominent factor influencing the level of acceptance of feminitves is regularity of their formation and clarity as to what the correct feminine form of a given name sounds like. It is also assumed that the greater frequency of use of given lexemes in public space increases their acceptance among individual language users. Henceforth, it can be infered that inclusive communication strategies used by university institutions may contribute to greater acceptance of feminitives in the student community.